Autoimmunization with Irradiated Tumour Cells in Human Malignant Melanoma. Issue 5712 (27th June 1970) - Ikonopisov, R. L.; Lewis, M. G.; Hunter-Craig, I. D.; Bodenham, D. C.; Phillips, T. M.; Cooling, C. I.; Proctor, J.; Fairley, G. Hamilton; Alexander, P.
Abstract : Thirteen patients have been immunized with their own irradiated melanoma cells on one or more occasions. Following these autografts tumour-specific cytotoxic antibodies were produced, the longest response lasting 14 days. This procedure had no apparent effect on the course of the disease in these patients.